Evaluating the maximum rate of penetration for drilling borehole in soft coal seam. Issue 9 (5th June 2020) - Yang, Shuo; Wen, Guangcai; Yan, Fazhi; Zhang, Mingjie; Zhao, Xusheng
Abstract: Most coal seams in China are characterized by high‐gas pressure and high‐gas content, which seriously threaten the safety of coal mines. Gas extraction is an effective measure for preventing gas disasters. However, the drilling process in soft coal seams is inefficient; it is difficult for the boreholes to reach the design length. The rate of penetration (ROP) plays an important role in determining drilling efficiency and borehole length in soft coal seams. In this study, we establish a simplified ROP model for soft coal seams and evaluate the maximum ROP of Hebi No. 6 coal mine. First, the drill cutting transport capacity of the drilling system and drill cutting quantity generated during the drilling process are analyzed. By simplifying drill cutting transport and coal seam properties, the ROP model is established. Second, the Rock Failure Process Analysis software is used to analyze the deformation region of boreholes, which has a great influence on the drill cutting transport space. Finally, a field test is implemented in Hebi No. 6 coal mine in Henan Province, China, to verify the model, and we propose a measure to control the ROP below the maximum value to increase the length of the borehole. The test results indicate that the model has high accuracy, with errors less than 15%, and the lengths of boreholes in air‐return and transportation roadways are increased to 60 and 80 m, respectively, and the increase rate is greater than 50%. Abstract : We establish a simplified ROP model and evaluate the maximum ROP, and the results indicate that the model has high accuracy and the lengths of boreholes are increased.